Accessibility and Effectiveness of Qur’anic Braille Instruction for Visually Impaired Students: A Case Study at BUKESRA, Banda Aceh - Roslaili, Yuni; Munandar, Aris; Mukdin, Khairani; Suparwany, Suparwany; Rahmi, Maulidatun (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This study aims to analyze the accessibility and effectiveness of Qur'anic Braille instruction for blind students at SDLB Bukesra Ulee Kareng, Banda Aceh. Employing a qualitative approach with a case study method, data were collected through interviews, observations, and questionnaires. The findings reveal that the school has developed an effective inclusive learning system by providing Braille Qur'ans and implementing various teaching methods such as A-to-Z, Synthetic Structural Analysis (SAS), left-code technique, and talaqqi. Teachers also offer individualized support to address learning challenges. Students generally master reading and writing the Qur'an in Braille within an average of three months and have achieved recognition in local Braille Qur'an reading competitions. Nevertheless, the study identifies several challenges, including limited availability of Braille Qur'ans in the dormitory, the absence of the “Nun Wiqayah” symbol in Braille scripts, and a shortage of trained professionals. These findings highlight the need for enhanced resources and institutional support to optimize Qur'anic learning for blind students.